2016
DOI: 10.1021/acsami.5b10985
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Free Oil Absorbents Made from Cellulose Nanofibril Aerogels

Abstract: Aerogels based on cellulose nanofibrils (CNFs) have been of great interest as absorbents due to their high absorption capacity, low density, biodegradability, and large surface area. Hydrophobic aerogels have been designed to give excellent oil absorption tendency from water. Herein, we present an in situ method for CNF surface modification and hydrophobic aerogel preparation. Neither solvent exchange nor fluorine chemical is used in aerogel preparations. The as-prepared hydrophobic aerogels exhibit low densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(96 citation statements)
references
References 46 publications
6
90
0
Order By: Relevance
“…Absorption of chloroform is almost two times as much as that of the pure sponge. Absorption capacity is obviously higher than many recent reported sorbents (Table 1), such as nitrogen-rich carbon aerogel10, CNT/PDMS coated PU sponge27, highly hydrophobic, fire-resistant (UHF) sponge30, cellulose nanofibril aerogels45 and micro-wrinkled reduced GO46. The capacity of hBN coated sponge is also higher than that of melamine sponge coated with exfoliated graphene (165 g.g −1 , or 153 g.g −1 )1523, reduced graphene (99 g.g −1 )24 and MoS 2 (159 g.g −1 )26.…”
Section: Resultsmentioning
confidence: 64%
“…Absorption of chloroform is almost two times as much as that of the pure sponge. Absorption capacity is obviously higher than many recent reported sorbents (Table 1), such as nitrogen-rich carbon aerogel10, CNT/PDMS coated PU sponge27, highly hydrophobic, fire-resistant (UHF) sponge30, cellulose nanofibril aerogels45 and micro-wrinkled reduced GO46. The capacity of hBN coated sponge is also higher than that of melamine sponge coated with exfoliated graphene (165 g.g −1 , or 153 g.g −1 )1523, reduced graphene (99 g.g −1 )24 and MoS 2 (159 g.g −1 )26.…”
Section: Resultsmentioning
confidence: 64%
“…An alternative strategy is to modify the NFC dispersions prior to the freeze or supercritical drying process. [108][109][110][111][112] In this way, the entire cellulose aerogel could be functionalized. For instance, Zhang et al 108 reported a facile process to prepare hydrophobic, exible, and low-density (#17.3 mg cm À3 ) cellulose aerogels by freeze-drying aqueous NFC suspensions with methyltrimethoxysilane (MTMS) as a silylating agent.…”
Section: Cellulose Nanomaterials and Wood For Oil/water Separation Anmentioning
confidence: 99%
“…It can be obtained from wood pulp, cotton, hemp, and some species of bacteria. In recent years, cellulose nanofibrils (CNFs) extracted from cellulose pulp have become a promising candidate for environmental applications because of their high surface areas, high aspect ratios, and biodegradability . For example, Chin et al prepared CNFs from kenaf core .…”
Section: Adsorbent Materialsmentioning
confidence: 99%